Perception and attitude towards tree growing in east Nepal - Das, Annapurna N. (Banko Janakari, 2017)
Information on existing tree growing practices were collected from seven villages of Morang District and six that of Dhankuta through Rural Appraisals. The tree species that the rural households were willing to introduce into their farmland have been listed. Results indicated that there is a common interest among rural households of both the Terai and Middle Hills towards growing bamboo in private farmlands. Rural households in the Terai preferred timber species such as sissoo (Dalbergia sissoo) and fruit trees which have high commercial values, whereas Middle Hills households preferred fodder trees.